La suscripción a obras literarias en España en la segunda mitad del siglo XVIII: libreros e instituciones - Buigues, Jean-Marc (My University, 2019)
This paper analyzes book subscriptions in Spain through fourteen works of literature from the second half of the eighteenth century. Works by Torres Villarroel, Tomás de Iriarte, Lope de Vega, Ramón de la Cruz, Capmany, Vaca de Guzmán, Castrillón, and Don Quixote, and translations of English novels from the end of the century, constitute the corpus. These are analyzed under a double approach: through professional subscribers (booksellers, printers, and retailers) and institutional subscribers (libraries of convents, academies, universities, and schools., Este trabajo pretende analizar las suscripciones en España a catorce obras de literatura en la segunda mitad del siglo XVIII. Obras de Torres Villarroel, Tomás de Iriarte, Lope de Vega, Ramón de la Cruz, Capmany, Vaca de Guzmán, Castrillón y el Quijote, y traducciones de novelas inglesas finiseculares constituyen el corpus analizado bajo un doble enfoque; el de los suscriptores profesionales (libreros, impresores y comerciantes) y el de las suscripciones institucionales (bibliotecas de conventos, academias, universidades y escuelas).
Subscriptions to Literary Works in Spain During the Second Half of the Eighteenth Century: Booksellers and Institutions
Keywords: Subscription; Printed Books; Literature; Eighteenth Century; Spain; Suscripción; impresos; literatura; siglo XVIII; España